Children's Consonant Acquisition in 27 Languages: A Cross-Linguistic Review - McLeod, Sharynne; Crowe, Kathryn (American journal of speech-language pathology, 2018)
The aim of this study was to provide a cross-linguistic review of acquisition of consonant phonemes to inform speech-language pathologists' expectations of children's developmental capacity by (a) identifying characteristics of studies of consonant acquisition, (b) describing general principles of consonant acquisition, and (c) providing case studies for English, Japanese, Korean, and Spanish. A cross-linguistic review was undertaken of 60 articles describing 64 studies of consonant acquisition by 26,007 children from 31 countries in 27 languages: Afrikaans, Arabic, Cantonese, Danish, Dutch, English, French, German, Greek, Haitian Creole, Hebrew, Hungarian, Icelandic, Italian, Jamaican Creole, Japanese, Korean, Malay, Maltese, Mandarin (Putonghua), Portuguese, Setswana (Tswana), Slovenian, Spanish, Swahili, Turkish, and Xhosa. Most studies were cross-sectional and examined single word production. Combining data from 27 languages, most of the world's consonants were acquired by 5;0 years;months old. By 5;0, children produced at least 93% of consonants correctly. Plosives, nasals, and nonpulmonic consonants (e.g., clicks) were acquired earlier than trills, flaps, fricatives, and affricates. Most labial, pharyngeal, and posterior lingual consonants were acquired earlier than consonants with anterior tongue placement. However, there was an interaction between place and manner where plosives and nasals produced with anterior tongue placement were acquired earlier than anterior trills, fricatives, and affricates. Children across the world acquire consonants at a young age. Five-year-old children have acquired most consonants within their ambient language; however, individual variability should be considered. https://doi.org/10.23641/asha.6972857.